A Special Issue of CIT based on the best papers at the 2010 annual conference International Conference on Information Technology Interfaces (ITI) - Mladenić, Dunja; Paul, Ray, J.; Tadić, Marko (2010)
Editorial to the special issue of the Journal of computing and information technology based on the best papers at the 2010 annual conference International Conference on Information Technology Interfaces (ITI).
Projekt MZOS
ENG